Pharmacological prevention of fibrosis in dacryosurgery - Atkova, E L; Krakhovetskiy, N N; Fokina, N D; Murakhovskaya, Yu K; Kulish, K K; Avagyan, A S; Smirnova, N S (Vestnik oftal'mologii, 2024)
Chronic inflammatory process in the lacrimal drainage system is the main etiological factor leading to dacryostenosis and consequent obliteration - partial and total nasolacrimal duct obstruction. Prevention of this process is an urgent problem in dacryology. Currently, there is very little research on the development and use of conservative methods for treating dacryostenosis using anti-inflammatory, as well as anti-fibrotic drugs. In this regard, the main method of treating lacrimal drainage obstruction is dacryocystorhinostomy. However, the problem of recurrence after this operation has not been resolved. The causes of recurrence can be cicatricial healing of dacryocystorhinostomy ostium, canalicular obstruction, formation of granulations and synechiae in its area. Surgical methods of recurrence prevention are associated with possible complications, and there is conflicting data on the feasibility of their use. Based on this, the development of pharmacological methods for the prevention of fibrosis in dacryology is promising, among which the antitumor antibiotic Mitomycin C is the most studied. However, there are no specific scientifically substantiated recommendations for the use of this drug, and the data on its effectiveness vary. This has prompted researchers to look for and study alternative anti-fibrotic agents, such as antitumor drugs, glucocorticoids, hyaluronic acid, small molecule, biological, immunological and genetically engineered drugs, as well as nanoparticles. This review presents the current data on the efficacy and prospects of the use of these drugs in dacryology.